Receiver Temperature Control Of The Parabolic Dish Stirling Engine - Liaw, Geok Pheng; Ab Ghani, Mohd Ruddin; Affandi, Rosnani; Gan, Chin Kim; Jano, Zanariah (MAGNT RESEARCH REPORT, 2015)
Parabolic Dish (PD) system is one of the Concentrating Solar Power (CSP) technologies that converts the thermal energy from solar irradiance into mechanical energy and then to electrical energy. The concentrator in PD system works by focusing the solar radiation onto the receiver located at the focal point. The solar power that is produced from the concentration process is intercepted by the receiver and then used for the energy conversion process in PD system to generate electricity. Power conversion unit (PCU) of a dishStirling (DS) system is to maintain the absorber temperature within a safe operating region. The temperature should be kept as high as possible to maximize the thermal efficiency of the Stirling engine, but should not also exceed the thermal rating of the absorber material. However, this study is carried out to design and analyse the control system for parabolic dish-stirling (PD) system and the results from this study are useful for a better understanding of the system efficiency.